Multiscale Transcriptomic Integration Reveals B-Cell Depletion and T-Cell Mistrafficking in Nasopharyngeal Carcinoma Progression - Shi, Xiaojie; Pan, Junyan; Qiu, Fufang; Wu, Liqin; Zhang, Xuyan; Feng, Yan; Gu, Xiaoyi; Zhao, Jikuang; Zheng, Wenwei (Frontiers in Cell and Developmental Biology, 2022)
Nasopharyngeal carcinoma (NPC), featured by Epstein-Barr virus (EBV) infection and regional epidemiology, is curable when detected early, but highly lethal at an advanced stage. The molecular mechanism of NPC progression toward a clinically uncontrollable stage remains elusive. In this study, we developed a novel computational framework to conduct multiscale transcriptomic analysis during NPC progression. The framework consists of four modules enabling transcriptomic analyses spanning from single-cell, bulk, microenvironment, to cohort scales. The bulk-transcriptomic analysis of 133 NPC or normal samples unraveled leading functional enrichments of cell-cycle acceleration, epithelial-mesenchymal transition, and chemokine-modulated inflammatory response during NPC progression. The chemokine CXCL10 in the NPC microenvironment, discovered by single-cell RNA sequencing data analysis, recruits cytotoxic T cells through interacting with its receptor CXCR3 at early but late stages. This T-cell mistrafficking was featured by the decline of cytotoxic T cells and the increase of regulatory T cells, accompanied with B-cell depletion confirmed by immunohistochemistry staining. The featured immunomodulatory chemokines were commonly upregulated in the majority of cancers associated with viral or bacterial infections.